Sobre a formação de professores de matemática em Cuiabá - MT (1960-1980) - Both, Bruna Camila [UNESP] (2014)
This present research aims to compose a historic version about the formation of Mathematics professors, between the decades 1960 to 1980, in Cuiaba, Mato Grosso. To do this, we will seek to develop understandings about courses for teachers in this area, available in the region and period above mentioned, building relations with the current educational policies. As methodology adopted in order to meet our proposal, we made use of Oral History, through which we constitute narratives that along written and image sources, enabled us to compose our analysis, highlighting, as much as possible and/or necessary, convergences/divergences between them, in order to form our narrative for training of Mathematics professors in Cuiaba, formulated from different voices, sources and perspectives. Our research also aims to contribute to the larger project of Mapping of the Formation and Activities of Mathematics Professors in Brazil, from the group of Oral History and Mathematics Education, GHOEM, of which we are part